Binding of Host Factors Influences Internalization and Intracellular Trafficking of Streptococcus uberis in Bovine Mammary Epithelial Cells - Raul A. Almeida; John R. Dunlap; Stephen P. Oliver (Veterinary Medicine International)
We showed that internalization of Streptococcus uberis into bovine mammary epithelial cells occurred through receptor- (RME) and caveolae-mediated endocytosis (CME). We reported also that treatment of S. uberis with host proteins including lactoferrin (LF) enhanced its internalization into host cells. Since the underlying mechanism(s) involved in such enhancement was unknown we investigated if preincubation of S. uberis with host proteins drives internalization of this pathogen into host cells through CME. Thus, experiments involving coculture of collagen-, fibronectin-, and LF-pretreated S. uberis with bovine mammary epithelial cells treated with RME and CME inhibitors were conducted. Results showed that internalization of host proteins-pretreated S. uberis into mammary epithelial cells treated with RME inhibitors was higher than that of untreated controls. These results suggest that pretreatment with selected host proteins commits S. uberis to CME, thus avoiding intracellular bactericidal mechanisms and allowing its persistence into bovine mammary epithelial cells.